PENGARUH LUAS LAHAN, KURS DOLLAR AMERIKA, INDEKS HARGA PERDAGANGAN BESAR TERHADAP EKSPOR TEH INDONESIA TAHUN 2000 – 2015 - Suhartawan, Ketut Ari; Sudirman, Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 7, Juli 2018 (pp. 1352-1586), 2018)
One of the potential export commodities in Indonesia is tea. This study aims to determine the effect of land area, US dollar exchange rate, big trade price index simultaneously and partially to export Indonesian tea in 2000 - 2015. Data used is secondary data. The analysis technique used is multiple linear regression analysis. Test results shows that simultaneously variable of land area, US dollar exchange rate and big trade price index (IHPB) have significant effect to Indonesian tea export in 2000-2015. In partial land area have positive and significant effect to Indonesian tea export year 2000-2015. The coefficient of land width variable marked positive means that the more efficient use of agricultural land for the production process will increase the export value of Indonesian tea export. In pa r tial variable of US dollar exchange rate have positive and significant effect to Indonesian tea export year 2000-2015. The coefficient of US dollar exchange rate is positive so it can be concluded that the stronger the US dollar exchange rate, the export value will be higher. Partially IHPB variables have a positive and significant effect on Indonesian tea export in 2000-2015.